Systematic Review and Meta-Analysis of Preoperative Antisepsis with Combination Chlorhexidine and Povidone-Iodine - Davies, Benjamin M.; Patel, Hiren C. (The Surgery Journal, 2016)
Importance Effective preoperative antisepsis is recognized to prevent surgical site infection (SSI), although the definitive method is unclear. Many have compared chlorhexidine (CHG) with povidone-iodine (PVI), but there is emerging evidence for combination usage.Objective To conduct a systematic review and meta-analysis to evaluate if combination skin preparation (1) reduces colonization at the operative site and (2) prevents SSI compared with single-agent use.Data Sources A literature search of MEDLINE, Embase, and Cochrane Database of Clinical Trials was performed.Study Selection Comparative, human trials considering the combination use of CHG and PVI, as preoperative antisepsis, to single-agent CHG or PVI use were included. Studies were excluded from meta-analysis if the use or absence of alcohol was inconsistent between study arms.Data Extraction and Synthesis The study was performed using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines.Main Outcomes and Measures The primary outcome for meta-analysis was surgical site infection. The secondary outcome was colonization at the operative site.Results Eighteen publications with a combination of CHG and PVI use were identified. Of these, 12/14 inferred promise for combination usage, including four trials eligible for meta-analysis. Only one trial reported SSI as its outcome. The remaining three considered bacterial colonization. Combination preparation had a pooled odds ratio for complete decolonization of 5.62 (95% confidence interval 3.2 to 9.7, p < 0.00001). There was no evidence of heterogeneity (Cochran's Q 2.1, 2 df, p = 0.35).Conclusions and Relevance There is emerging, albeit low-quality, evidence in favor of combination CHG and PVI preoperative antisepsis. Further rigorous investigation is indicated.
Keywords: surgical site infection; surgical wound infection; antisepsis; chlorhexidine; povidone-iodine